2016
DOI: 10.1002/hbm.23396
|View full text |Cite
|
Sign up to set email alerts
|

Increases in brain activity during social competition predict decreases in working memory performance and later recall

Abstract: In our fMRI experiment, participants completed a learning task in both a noncompetitive and a socially competitive learning environment. Despite reporting a preference for completing the task while competing, participants remembered significantly more during the task and later recalled more from the noncompetitive learning environment. Furthermore, during working memory maintenance, there was performance-related deactivation in the medial prefrontal cortex (mPFC) and the precuneus/PCC. During feedback presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 87 publications
(165 reference statements)
1
5
1
Order By: Relevance
“…These results are consistent with previous findings that competition affects working memory performance (DiMenichi & Tricomi, 2015). Other studies (DiMenichi & Tricomi, 2016) have also concluded that decreased working memory performance during competition can be predicted by increased brain activity.…”
Section: Mixed Factorial Anova Pearson's R Ssim Jaccardsupporting
confidence: 92%
“…These results are consistent with previous findings that competition affects working memory performance (DiMenichi & Tricomi, 2015). Other studies (DiMenichi & Tricomi, 2016) have also concluded that decreased working memory performance during competition can be predicted by increased brain activity.…”
Section: Mixed Factorial Anova Pearson's R Ssim Jaccardsupporting
confidence: 92%
“…Cognitive load also appears to diminish people's ability to imagine themselves in another's perspective (Davis et al, 1996) and similar effects are observed in subjects with working memory deficits (Lin et al, 2010). Conversely, taking the perspective of another person has been shown to detract cognitive resources from concurrent behavioural performance (Vorauer et al, 2009) and working memory performance has been shown to be impaired during a competitive task likely to entail some degree of perspective taking (DiMenichi and Tricomi, 2017). All of these results are consistent with the notion that people process others' perspectives by serially and effortfully adjusting from their own, and are only able to do so when they have sufficient cognitive resources and are sufficiently incentivised to employ them.…”
Section: Cognitively Effortful Theory Of Mindmentioning
confidence: 81%
“…Additionally, behavioral results (see Supporting materials) revealed that during the outcome judgment task, RTs were longer for negative outcomes involving social comparison than for positive outcomes in the competition condition but not in the noncompetition condition as well as in the self‐positive condition but not in the self‐negative condition, suggesting longer RTs for negative outcomes involving social comparison only in the competition and self‐positive condition. It has been reported that competition impairs stimulus memory (DiMenichi & Tricomi, 2015, 2017; Liu et al., 2021). In addition, previous studies have also shown that memory of target stimuli is impeded by negative context (Lin et al., 2015; Lin & Liang, 2023a, 2023b).…”
Section: Discussionmentioning
confidence: 99%